2021
DOI: 10.1002/cncr.33879
|View full text |Cite
|
Sign up to set email alerts
|

Seizures' impact on cognition and quality of life in childhood cancer survivors

Abstract: BACKGROUND:The objective of this study was to determine the impact of seizure-related factors on neurocognitive, health-related quality of life (HRQOL), and social outcomes in survivors of childhood cancer. METHODS: Survivors of childhood cancer treated at St. Jude Children's Hospital (n = 2022; 48.3% female; median age, 31.5 years; median time since diagnosis, 23.6 years) completed neurocognitive testing and questionnaires. The presence, severity, resolution, and treatment history of seizures were abstracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Adult survivors of childhood cancer who reported fatigue were more likely to have cognitive impairment compared with those without fatigue . Other characteristics associated with cognitive impairment include sleep disruption, cardiopulmonary disease and endocrine dysfunction, higher cumulative anesthesia exposure, exercise intolerance, severe hearing impairment and seizures, and missed school instruction while receiving treatment for childhood cancer. Consistent physical activity in adult survivors of childhood cancer has been associated with fewer cognitive problems …”
Section: Discussionmentioning
confidence: 99%
“…Adult survivors of childhood cancer who reported fatigue were more likely to have cognitive impairment compared with those without fatigue . Other characteristics associated with cognitive impairment include sleep disruption, cardiopulmonary disease and endocrine dysfunction, higher cumulative anesthesia exposure, exercise intolerance, severe hearing impairment and seizures, and missed school instruction while receiving treatment for childhood cancer. Consistent physical activity in adult survivors of childhood cancer has been associated with fewer cognitive problems …”
Section: Discussionmentioning
confidence: 99%
“…Nonfebrile sei zures and cere bro vas cu lar stroke can occur dur ing front line ther apy for pedi at ric hema to logic malig nan cies and fur ther affect neurocognitive func tion. 15,16 The impact from these events is in addi tion to the risks asso ci ated with treat ment expo sures discussed above. It has been reported that severe infec tion and sep sis con fer addi tional risk for neurocog nitive impair ment on top of the known risk asso ci ated with CNS treat ment.…”
Section: Direct Neu Ro Tox Ic Itymentioning
confidence: 99%
“…Similarly, a high percentage of patients would report visual deficits, with a lower percentage of about 3% for cataracts to a higher proportion of patients complaining of diplopia (17%) [ 16 ]. Phillips et al suggest that pediatric CNS cancer survivors experience additional neurocognitive risk if they develop a seizure diagnosis, with seizure resolution associated with improved attention and memory [ 17 ]. In a large cohort of adults survivors of pediatric CNS tumors treated at St. Jude Children’s Research Hospital, the survivors with a history of seizures were at risk of severely impaired academics, attention, and memory dysfunction compared with those without a history of seizures, even after adjustment for cranial radiotherapy (CRT) exposure [ 18 ].…”
Section: Neurologic and Sensory Late Effectsmentioning
confidence: 99%
“…Vision impairment can also impact performance on some neuropsychological tests and needs to be considered as a risk factor before and after RT. Achieving seizure resolution is a crucial step toward improving neurocognitive outcomes in CNS cancer survivors [ 17 ].…”
Section: Strategy Of Monitoring and Potential Interventionmentioning
confidence: 99%